Peri-operative Considerations in Intracranial Hemorrhage in Dengue Virus Infected Patients: A Prospective Mini Case Series - Meena, Shyam C; Dulara, Suresh C; Gautam, Sachindanand; Beldar, Sharad (Nepal Journal of Neuroscience, 2016)
Dengue is one of the most common mosquito-transmitted arboviral diseases of tropical and few subtropical areas of the world. It is estimated that 100 million cases occur every year and 2.5 billion people are at risk. Hemorrhagic complications causing encephalopathy is quite a rare presentation but usually fatal. We discuss the peri-operative management of 8 uncommon cases of intracranial hemorrhage (ICH) in dengue. High index of suspicion is required for prompt diagnosis and treatment.Eighteen dengue serology positive patients who presented with neurological manifestations were managed in neurosurgery unit of our tertiary health care center in six months duration. Most of the patients had deranged prothrombin time and thrombocytopenia. They were given platelet concentrates for correction of thrombocytopenia. All vital parameters and neurologic status were closely monitored in high dependency unit. Eight of these patients had deterioration in neurologic status; five of them underwent surgery.All patients who underwent surgery had excellent outcome. Rest of the patients including one patient of cervical extradural hemorrhage were managed conservatively with intravenous fluid and cerebral decongestants. Two patients with deep-seated bleed deteriorated very rapidly and died. Rest who were managed either surgically or conservatively including cervical EDH improved well without any residual deficit.High index of suspicion of ICH is required in dengue especially during convalescence. Special attention should be given to those patients who are disoriented and have altered sensorium and should not be misinterpreted as fever delirium or toxic encephalopathy. It needs immediate attention and investigation. Timely diagnosis and intervention can save lives.Nepal Journal of Neuroscience 13:43-46, 2016